Investigation of the Rare Fraction of Flora in the Projected Landscape Reserve "Balka Shchurivska" - Svitlana Kyiak; Pavlo Kyiak (Kazimierz Wielki University, 2023)
The study investigates the current distribution of rare plant species within the ravine system "Balka Shchurivska" and provides justification for granting the site protected area status. The research examines the presence of rare plant species listed in the Red Book of Ukraine, the Red List of Dnipropetrovsk Oblast, and international conservation lists. Field surveys conducted from 2020-2023 revealed the presence of 26 regionally rare plant species, 13 species listed in the Red Book of Ukraine, 3 species from Resolution 6 of the Bern Convention and annexes of the Habitats Directive represented in Ukraine's flora, and 1 species from the IUCN Red List. Notable rare species found include Pulsatilla pratensis, Adonis vernalis, and Stipa capillata. The study highlights the importance of the area for biodiversity conservation and recommends its designation as a landscape reserve of national importance.